Dorsal plane-shaped advancement flap for the reconstruction of web space in syndactyly without skin grafting: A preliminary report. Issue 11 (November 2015) - Liu, Juan; Zheng, Huaiyuan; Chen, Zhenbing; Dai, Xinyi; Schilling, Arndt F.; Machens, Hans-Günther
Summary: Background: Skin grafting for syndactyly repair is time-consuming, and it has the potential risks of scar contracture and web creep. Several techniques have been described for web reconstruction without skin grafts in simple syndactyly. Based on the hexagonal advancement flap, we designed a "plane-shaped" advancement flap on the dorsal hand or foot for a web reconstruction with primary closure. Methods: Between June 2010 and August 2013, a "plane-shaped" advancement flap was used for web reconstruction in 24 syndactylies of 20 pediatric patients. The patients' age ranged from 1.5 to 8 years (mean age: 2.5 years). The patients were followed up for 15–48 months (mean: 28 months). Results: The mean operation time was 60 min (range: 50–75 min). All incisions were closed primarily without skin grafting. All the flaps survived completely without early complications such as infection, vascular compromise or delayed healing. The mean hospitalization time was 3.5 days. There was no occurrence of long-term complications including web creep, flexion contractures, angulation deformity, or obvious keloid formation during the 15–48 months follow-up. Cosmetic and functional satisfactory outcomes were achieved in all cases without secondary revision. Conclusion: The dorsal plane-shaped advancement flap without skin graft is a solution for web space reconstruction in simple syndactyly, especially in the foot.